Plants cultivated in Choco, Colombia, as source of repellents against Tribolium castaneum (Herbst) (2014)
Essential oils (EOs) of eight plants collected in Choco, Colombia, including Piper divaricatum, P. pseudolanceifolium, P. confertinodum, P. diazanum, Ocimum campechianum, Siparuna conica, Mikania micrantha and Hedychium coronarium, were analyzed by gas chromatography–mass spectrometry and tested as repellents against Tribolium castaneum, using the area preference method, after 2 and 4 h exposure. The main components found in Eos were methyl eugenol, trans-β-cariophyllene, methyl eugenol, α-pinene, δ-cadinene, γ-elemene, α-pinene and 1,8-cineol, for O. campechianum, P. pseudolanceifolium, P. divaricatum, P. confertinodum, P. diazanum, S. conica, M. micrantha, and H. coronarium, respectively. Best repellent activities were observed for oils from O. campechianum and P. pseudolanceifolium with mean repellent concentration (RC50) values of 0.00006 and 0.0001 μL/cm2 after 2 h, and 0.00003 and 0.0001 μL/cm2 after 4 h, respectively; whereas the least potent was that from M. micrantha, with RC50 values of 0.074 and 0.040 μL/cm2 at 2 and 4 h exposure times, respectively. Based on average percentage repellence, oils from P. pseudolanceifolium and O. campechianum were classified as Class IV repellents and were better than the commercial repellent IR3535, classified as Class II. These data evidence the Choco region as an important source of natural repellents with promising commercial opportunities.